Single‐Molecule and Ensemble Diffusivities in Individual Nanopores with Spatially Dependent Mobility. Issue 15 (14th June 2017) - Rybka, Julia; Kärger, Jörg; Tallarek, Ulrich
Abstract: We investigated single‐molecule and ensemble diffusivities in a silica nanopore with a chemically modified surface by molecular dynamics simulations. Solutes with graded polarity (nonpolar ethylbenzene and moderately polar benzyl alcohol) were equilibrated with a 40:60 v / v water/acetonitrile solvent in a 10 nm pore, the surface of which was rendered hydrophobic by modification with alkyl chains. Simulations enable detailed sampling of spatially dependent solvent and solute mobilities, which originate from microheterogeneity induced by the surface modification. Acetonitrile is enriched near the ends of the alkyl chains and forms a high‐mobility interface region between the (nonpolar) bonded phase at the surface and the (polar) bulk liquid in the center of the pore. Solvent and solute diffusivities calculated from the time average of a single molecule and from the ensemble average over all molecules, respectively, revealed excellent agreement, which implies validity of ergodicity. The molecular‐simulation approach to investigate the time average of a single molecule, on the one hand, and the ensemble average over a larger number of molecules, on the other hand, is general and can be adapted for a variety of surfaces, solvents, and solute molecules by using pores with tailored geometries and surface modifications. Abstract : Test of ergodicity for pore diffusion : Ergodicity is proven for single‐molecule and ensemble diffusivities of solvent and solute molecules in a silica nanopore with a hydrophobic surface modification. Molecular dynamics simulations allow quantification of the effects of spatially dependent mobility near the surface (which stems from the microheterogeneity induced by the nonpolar bonded phase) on the effective pore‐diffusion coefficient ( D pore ).